Our planet earth the global perspective - Lemle, Mickey; United Nations; Association of Space Explorers (Pennsylvannia : Bullfrog Films, 1990)
Astronauts and cosmonauts from ten different countries discuss their experiences and insights about the planet earth, in the hopes that all humanity will understand the wonder and fragility of the planet
Copy in DVD Format
Cameraman, Edward Marritz ; editor, Cari Comart ; music, Carman Moore
VHS Format
Keywords: Earth; Earth sciences